Development of the career adaptability across high school by student-athletes in Finland - Ojala, Juulia (2019)
Vocational development has been noticed to cover the whole lifespan, but especially important time period is the youth. The aim of this study was to examine, how does the career adaptability develop across high school by Finnish student-athletes. The second intent was to detect if there are different developmental profiles of career adaptability among this population. In addition, the relation between possible developmental profiles and dropout from sport as well as academic success were investigated. A total of 391 student-athletes, who were 16 years old on average in the beginning of the project, from seven sport high schools participated in this study. The participants filled in Career Adapt-Abilities Scale - Dual Career Form (CAAS-DC; Ryba & Aunola, 2015), which measures their career adaptability with five subscales, and a background information questionnaire, to assess their continuation of dual career and academic success. The data was analysed by using Multivariate Analysis of Variance (MANOVA), Kmeans cluster analysis, cross-tabulation, correlation matrix, and One-Way Variance Analysis (ANOVA). First, the results showed that the development of adaptability was different between measurement points, between subscales, and interaction between measurement points and subscales. The skills were strongest in the subscales of control and confidence, and weakest in the concern subscale. Secondly, four different developmental profiles were found: high, low, increasing, and decreasing. In the high and low profiles, the adaptability stayed permanent, whereas in the increasing and decreasing profiles, the adaptability developed either more or less than on average. A relation between adaptability and dropping out of sport was found; lower adaptability skills were related to dropping out. There was also a relation between academic success and adaptability; stronger adaptability skills related to better academic success. This relation generalized across time from considering only the confidence subscale to covering all other subscales except curiosity in the end. The study findings gave new information about the development of career adaptability, because there is only little longitudinal research about this issue. In addition, the results demonstrate that the career adaptability develops individually, which should be considered when designing and addressing support.